PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DALAM PEMILIHAN SISWA PENERIMA DANA BANTUAN DI SMA PURNAMA TRIMURJO - Wati, Sindi Jamila; Sutomo, Budi (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
In this study the author aims to help parties SMA Purnama Trimurjo to select recipients of aid funds using the method Simple Adicvity weighting (SAW). There are three criteria that the author uses, namely the income of the parents, the work of the parents and the number of dependents. Considering that so far no particular method has been used in selecting poor students so that sometimes decisions are considered less efficient and not well targeted. Based on the criteria that have been determined using the research method SAW is carried out by looking for the weight value of each attribute, then a student selection process is carried out which will determine, namely poor student.